The role of Denisons organisational culture on email usage among academician in Malaysian private universities - Mohamed, Anuar Shah Bali; McGrath, Michael G.; Bong, Zhi Yuh; Othman, Zulbasri; Sheikh Mokhtar, Siti Salwa (Science Publishing Corporation, 2018)
Academician in Malaysian private universities. For the research, a scale of measurement was used based upon the concepts that are found in values as well as practices in regards to organisational culture developed by Denison and Mishra (1995) model namely Involvement- Capability Development (ICD), Consistency-Agreement (CA), Adaptability-Organisational Learning (AOL) and Mission- Goals & Objectives (MGO). In this study, Technology Acceptance Model (TAM) developed by Davis (1989) was used as part of the perspective theory on technology adoption, using the constructs; perceived ease of use (PEOU) and perceived usefulness (PU) as mediator for organisational culture and email usage. Data used in the study were based on questionnaires of 128 academician from two Malaysian private universities. The study found that all constructs of organisational culture were having significant in the relationship to the perceived ease of use (PEOU) and perceived usefulness (PU) with ICD, AOL and MGO having significant positive relationship with PEOU and PU while CA has significant negative relationship with PEOU and PU on email usage. Finally, PU and PEOU had significant positive relationship with email usage while PEOU had significant positive relationship with PU on email usage. This means that the usage of email among academician in Malaysian private universities depend on both the user’s perception of email usefulness and the perception of ease of use.